Clinical Presentation and Course of Pulmonary Involvement in Chronic Nonbacterial Osteomyelitis - Toni Hospach; Friederike Blankenburg; Anita Heinkele; Kristina Rücklová; Peter Müller‐Abt; Frank Weller‐Heinemann; Laura Buchtala; Jan Maier; Jasmin Kümmerle‐Deschner; Christiane Reiser; Ales Janda; Andreas Urban; et al. (ACR Open Rheumatology)
Objective Pulmonary involvement in chronic nonbacterial osteomyelitis (CNO) is rare. Limited awareness results in diagnostic challenges, especially because malignancy or infection needs to be considered. Methods Based on a survey shared among centers participating in the Kerndokumentation Deutsches Rheumaforschungszentrum (Germany), this study investigated clinical and imaging presentations, demographic features, treatment response and outcomes of pulmonary involvement in CNO (pCNO). Magnetic resonance imaging and computed tomography images were read centrally by an experienced pediatric radiologist. Results Twenty‐two patients with pCNO were included in this study. Among patients with CNO, pulmonary involvement was more common in girls (91% vs 62.8%, P = 0.006) and patients with multifocal bone lesions (95% vs 65%, P <0.001) but was not associated with systemic inflammation or additional organ involvement. Forty‐two pulmonary lesions were counted with a median of two per patient (two to six). They displayed a median size of 1.8 cm (0.3–4.0 cm) and followed mono‐ (40%) and oligo‐focal (60%) patterns representing consolidations or nodules, abutting the pleura in 50%. Although prominent hilar lymph nodes were present (in 19% of patients), no pathologic enlargement (>1 cm) was seen. When available (3 of 22 patients), histology revealed granulomatous inflammation with lymphocyte infiltration. Development and courses of pCNO did not associate with treatments chosen. Complete remission was reported in 60% of patients, partial remission in 20%. Conclusion pCNO is usually asymptomatic. Although more common in girls and patients with multifocal CNO, pCNO is not associated with systemic parameters of inflammation or specific organ involvement. Prognosis of pCNO is favorable, and most lesions resolve over time. Thus, a careful watch‐and‐wait strategy may be appropriate.